BUSINESS PROCESS OUTSOURCING AS A COMPETITIVE STRATEGY FOR U.S. STARTUPS - Testoni, Felipe Oscar (Revista Sistemática, 2021)
In today’s competitive entrepreneurial landscape, U.S. startups are increasingly leveraging Business Process Outsourcing (BPO) as a strategic tool to overcome operational constraints and accelerate growth. This paper explores the key advantages of BPO for early-stage ventures, including cost reduction, access to specialized expertise, improved scalability, and enhanced focus on core competencies. Through industry data and real-world case studies such as Slack, GitHub, and Basecamp, the research highlights how outsourcing enables startups to streamline operations and remain agile in volatile markets. It also examines the role of technological advancements, globalization, and best practices that ensure sustainable partnerships with outsourcing providers. The findings demonstrate that, when strategically implemented, BPO not only offers operational relief but serves as a long-term competitive differentiator for startups navigating growth and innovation in the U.S. economy.